Analisis Literasi Keuangan Syariah pada Masyarakat Desa Tinatar Terhadap Produk Pembiayaan Syariah Ditinjau Perspektif Maqashid Syariah - Leny Sukmawati; Subkhan Alimuddin (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study aims to analyze the level of Islamic financial literacy of the Tinatar Village community and identify the factors causing the low adoption of Islamic financing products, viewed from the perspective of maqashid sharia. This study uses a descriptive qualitative approach with data collection techniques in the form of in-depth interviews and participatory observations of 15 informants. The data were analyzed using thematic analysis methods and measured based on five indicators of Islamic financial literacy according to OJK, namely financial knowledge, financial skills, financial beliefs, financial attitudes, and financial behavior. The results of the study showed that most informants were in the Less Literate and Not Literate categories. The main factors influencing low literacy include lack of education and socialization, limited access, and the influence of culture and education levels and the dominant preference for conventional products which are considered easier and more familiar. The perspective of maqashid sharia shows that these conditions do not fully support the realization of protection for religion (ḥifẓ al-dīn), soul (ḥifẓ al-nafs), reason (ḥifẓ al-‘aql), descendants (ḥifẓ al-nasl), and property (ḥifẓ al-māl). Therefore, an integrated education and social intervention strategy is needed with the values of maqashid sharia, involving community leaders, sharia financial institutions, and an approach that is appropriate to the culture and context of rural communities.